1985
DOI: 10.1159/000146053
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Kinetics Affect Langerhans’ Cells of Mouse Vaginal Epithelium

Abstract: Langerhans’ cells were found to vary in their morphology and density in the vaginal epithelium of ovariectomized mice stimulated by single daily injections of oestrogen. In ATPase-stained epithelial sheet preparations, Langerhans’ cells were small and stellate in dense distribution after ovariectomy produced epithelial atrophy. They became highly dendritic in sparse distribution as epithelial thickness increased with high mitotic activity. Keratinization when prolonged by daily oestrogen injections did not aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

1986
1986
2003
2003

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 12 publications
1
8
1
Order By: Relevance
“…The cells changed from small stellate to highly dendritic cells under these conditions. This was in accordance with previous findings [Young, 1985]. Fur thermore, the removal of keratin by vitamin A from the oestrogen-stimulated epithelium did not reduce the epithelial thickness or alter the Langerhans cell mor phology or distribution.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The cells changed from small stellate to highly dendritic cells under these conditions. This was in accordance with previous findings [Young, 1985]. Fur thermore, the removal of keratin by vitamin A from the oestrogen-stimulated epithelium did not reduce the epithelial thickness or alter the Langerhans cell mor phology or distribution.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies of Langerhans cells in the epithelial hyperplasia and keratinization in the murine vaginal epithelium have established that Langerhans cells vary in their morphology and distribution per mm2 of epi thelium in oestrogen-stimulated epithelium in ovariec tomized animals [Young, 1985], The cells become more dentritic and are more sparsely distributed when the epithelium is thickening and expanding by mitotic activ ity. They become less dendritic and are closer together when the epithelium is thin and the mitotic activity low.…”
Section: Introductionmentioning
confidence: 96%
“…The frequency of LCs also was reported to vary inversely with the degree of keratinization in rodent (Hill, 1977) and human (Daniels, 1984) oral epithelium; in contrast, a direct correlation was found in oral tissues of the rhesus monkey (Hutchens et al, 1971). Other investigators have observed an inverse relationship between the density of LCs and epithelial thickness, both in epidermis that becomes hyperplastic when stripped of the horny layer (Lessard et al, 1968;Potten and Allen, 1975) and in vaginal epithelium (Young, 1985;Young et al, 1985), which undergoes a series of changes during the estrous cycle (Bertalanffy and Lau, 1963).…”
Section: Discussionmentioning
confidence: 97%
“…The distribution, density, and morphology of LCs may be affected by epithelial kinetics and patterns of keratinization (Schweizer, 1981). For instance, an inverse relationship between the density of LCs and epithelial thickness has been reported, both in tape-stripped, hyperplastic epidermis (Potten and Allen, 1975) and in vaginal epithelium during the estrous cycle (Young, 1985;Young et al, 1985). Since embryonic and fetal LCs are known to express specific, identifiable surface markers (Foster et al, 1986), the developing epidermis can provide a useful model for studying the LC population in association with epidermal kinetics during ontogeny.…”
Section: Introductionmentioning
confidence: 99%
“…Increased hydration also raises the friction coefficient of vulvar skin (27), which may make the vulva more susceptible to mechanical damage. (48,49) keratinized and non-keratinized regions of the vulva (6) those in keratinized skin (7) keratinized skin (7) No impact of menstrual cycle (8) Hydration Exposed skin is subject to drying effects of the environment More hydrated than exposed skin, based on trans-epidermal water loss (TEWL) (13,14) Hydrated Based on the mechanisms of skin penetration, the comparatively greater hydration of vulvar skin will affect tissue permeability in a manner that depends on the physicochemical nature of the solute and the applied vehicle (28)(29)(30)(31)(32)(33). For example, labia majora skin was more reactive than forearm skin to high concentrations of polar irritants (maleic acid and benzalkonium chloride) (34), but less reactive to dilute concentrations of the model irritant, sodium lauryl sulphate (35)(36)(37).…”
Section: Commentsmentioning
confidence: 99%